Latin American interventions in children and adolescents’ sedentary behavior: a systematic review - Ribeiro, Evelyn Helena Corgosinho; Guerra, Paulo Henrique; Oliveira, Ana Carolina de; Silva, Kelly Samara da; Santos, Priscila; Santos, Rute; Okely, Anthony; Florindo, Alex Antonio (Revista de Saúde Pública, 2020)
OBJECTIVE: To identify and evaluate the effects of community-based interventions on the sedentary behavior (SB) of Latin American children and adolescents. METHODS: A systematic review on community-based trials to reduce and/or control SB in Latin American countries (Prospero: CRD42017072157). Five databases (PubMed, Web of Science, Scopus, SciELO and Lilacs) and a reference lists were searched. RESULTS: Ten intervention studies met the eligibility criteria and composed the descriptive synthesis. These studies were conducted in Brazil (n=5), Mexico (n=3), Ecuador (n=1) and Colombia (n=1). Most interventions were implemented in schools (n=8) by educational components, such as meetings, lessons, and seminars, on health-related subjects (n=6). Only two studies adopted specific strategies to reduce/control SB; others focused on increasing physical activity and/or improving diet. Only one study used an accelerometer to measure SB. Seven studies investigated recreational screen time. Eight studies showed statistically significant effects on SB reduction (80%). CONCLUSIONS: Latin America community-based interventions reduced children and adolescents’ SB. Further studies should: define SB as a primary outcome and implement strategies to reduce such behaviour; focus in different SBs and settings, other than recreational screen time or at-home sitting time; and use objective tools together with questionnaires to measure sedentary behaviour in.